The shattered tree [compact disc, unabridged] - Todd, Charles (Todd, Charles. Bess Crawford mystery, 2016)
At the foot of a tree shattered by shelling and gunfire, stretcher-bearers find an exhausted officer, shivering with cold and a loss of blood from several wounds. The soldier is brought to battlefield nurse Bess Crawford's aid station, where she stabilizes him and treats his injuries before he is sent to a rear hospital. The odd thing is, the officer isn't British, he's French. But in a moment of anger and stress, he shouts at Bess in German. When the French officer disappears in Paris, it's up to Bess, a soldier's daughter as well as a nurse, to find out why, even at the risk of her own life.